2013
DOI: 10.20965/jdr.2013.p0243
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Analysis for Evaluation of Local Site Effects in Lima City, Peru from Ground Motion Data by Using the Spectral Inversion Method

Abstract: Effects of local site, propagation path and source in ground motion records observed in Lima, Peru, were separated by the spectral inversion method proposed by Iwata and Irikura (1986 [1], 1988 [2]) to examine the relation between local subsurface conditions and local site amplifications in a frequency range from 0.5 to 20 Hz. S-wave portions of accelerograms in horizontal components observed at 5 stations for 11 events along the Pacific coast of Lima city, Peru, were analyzed. The Q factor was obtained from o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Group 1 studies seismic motion and geotechnical aspects through seismic and microtremor observations at the case study sites. Together with existing geological data and newly conducted borehole surveys, the soil amplification characteristics have been investigated [5][6][7].…”
Section: Sourcementioning
confidence: 99%
“…Group 1 studies seismic motion and geotechnical aspects through seismic and microtremor observations at the case study sites. Together with existing geological data and newly conducted borehole surveys, the soil amplification characteristics have been investigated [5][6][7].…”
Section: Sourcementioning
confidence: 99%
“…Both PUCP and CER sites, which are located on alluvial gravel, show several peaks at frequencies above 3 Hz, corresponding to the site response of the Lima conglomerate. Using strong ground motion data, Quispe et al (2012) [14] reported that this deposit suffers from high amplification at frequencies larger than 4 Hz. The PUCP site shows a small bump between 1 and 2 Hz, which is also identified in the observed H/V spectral ratio of the microtremor data (Fig.…”
Section: Site Amplificationmentioning
confidence: 99%